Hairy root culture: A reliable bioreactor from transgenic plants - Shaharuddin, Noor Azmi; Atabaki, Narges; Nulit, Rosimah; Ahmad, Siti Aqlima; Malik, Sonia; Vahedi, Maryam; Kalhori, Nahid; Abiri, Rambod (Elsevier, 2024)
Plants can produce diverse arrays of specialized metabolites with different biological activities, which are used as raw materials in cosmetics, flavors, fragrances, pigments, and pharmaceutical industries. However, their production is quite low due to the limited availability of tissue and the complex pathways involved. Hairy root culture (HRC) is an alternative technique to produce these compounds of interest under in vitro conditions. Hairy roots, also known as transformed roots, are a fast-growing system with genetic and biochemical stability. They have also been applied as an economical technique in phytoremediation to remove environmental pollutants. They utilize multienzyme biosynthetic pathways and display highly efficient micropropagation and genetic engineering procedures. The present review summarizes the different biotechnological tools to harness the potential of the HRC system for various applications, especially the production of specialized metabolites and phytoremediation. Studies using omics, multigene engineering, elicitation, and nanoparticles for efficient utilization of HRC systems, keeping in view the susceptible and recalcitrant plants for hairy root induction, are highlighted. Finally, bottlenecks for upscaling hairy roots to foster the production of specialized metabolites and future prospectives are outlined.